Trust : who or what might support us? - Peperzak, Adriaan Theodoor, 1929- (Fordham University Press, 2013)
This study begins by presenting trust as a characteristic form of interpersonal and communal relationship. In the second chapter, the scope is narrowed to someone's reliance on one or more trustworthy individuals. Chapters 3 to 5 explore specific aspects of trust, insofar as we confide in social structures or movements, the impersonal regularities and events of nature, or our own particular talents, motivations, and possibilities.